Host and parasite morphology influence congruence between host and parasite phylogenies. Issue 8 (July 2018) - Sweet, Andrew D.; Bush, Sarah E.; Gustafsson, Daniel R.; Allen, Julie M.; DiBlasi, Emily; Skeen, Heather R.; Weckstein, Jason D.; Johnson, Kevin P.
Graphical abstract: Highlights: Brueelia -complex lice and their hosts show significant phylogenetic congruence. There is variation in the levels of congruence within this host–parasite system. Host dichromatism and louse ecomorphology can explain patterns of congruence. Host body size, plumage traits, and biogeography are not associated with congruence. Abstract: Comparisons of host and parasite phylogenies often show varying degrees of phylogenetic congruence. However, few studies have rigorously explored the factors driving this variation. Multiple factors such as host or parasite morphology may govern the degree of phylogenetic congruence. An ideal analysis for understanding the factors correlated with congruence would focus on a diverse host–parasite system for increased variation and statistical power. In this study, we focused on the Brueelia -complex, a diverse and widespread group of feather lice that primarily parasitise songbirds. We generated a molecular phylogeny of the lice and compared this tree with a phylogeny of their avian hosts. We also tested for the contribution of each host–parasite association to the overall congruence. The two trees overall were significantly congruent, but the contribution of individual associations to this congruence varied. To understand this variation, we developed a novel approach to test whether host, parasite or biogeographic factors were statistically associated with patterns of congruence. Both host plumage dimorphism and parasite ecomorphology were associated with patterns of congruence, whereas host body size, other plumage traits and biogeography were not. Our results lay the framework for future studies to further elucidate how these factors influence the process of host–parasite coevolution.